THE IMPACT OF MONETARY EXECUTION ON STOCK RETURN OF NON-BANKING ORGANIZATIONS IN INDONESIA - Sheila Najla Syahirah; Muhamad Deni Johansyah; Susan Purnama (International Journal of Quantitative Research and Modeling, 2023)
This study means to exactly analyze the impact of monetary execution proportions comprising of return on resources (ROA), return on value (ROE), current proportion (CR), the obligation to value proportion (DER), and financial worth added (EVA). to stock returns. The information utilized in this study is optional information, which was gotten from an outsider. The example in this study was chosen utilizing purposive examining which means getting an example as per the ideal measures. The populace in this study is non-banking organizations recorded on the LQ 45 File and the Sri Kehati File on the Indonesia Stock Trade (IDX) from 2015 to 2021. In light of the choice of tests by purposive examining, from various organizations that are individuals from the LQ 45 Record and Sri File Mindfulness, acquired the general example taken is 46 non-banking organizations. The logical model utilized in this study is a various straight relapse model. Concurrent exploration results show that all free factors fundamentally affect stock returns. Somewhat, the ROA, ROE, CR, and DER factors altogether affect stock returns. In the meantime, the EVA variable doesn't altogether affect stock returns.